Pengembangan Media Pembelajaran Sejarah Video Animasi dengan Karakter Loomie pada Materi Perang Dingin untuk Siswa Kelas XII MAN 1 Pontianak: Penelitian - Tegar Kurnia Rachman; Ika Rahmatika Chalimi; Edwin Mirzachaerulsyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to form a learning media in the form of animated videos using loomie characters in learning the history of Cold War material which is reviewed from the validation of material experts and media experts, and find out the feasibility. the type of research used is Research&Develoment. The mechanism of this study uses a simplified Borg and Gall model as 7 stages, namely, potential problems, data collection, Product Design, Design Validation, design revision, product testing and, product revision. Validation was obtained from material experts as much as 94.2% with a very decent classification and media experts as much as 87.2%. The results obtained from small group trials as much as 82.4%, and in large group trials as much as 88% with a very feasible category. According to the validation results of material experts and media experts, small group trials and large group trials, the development of animated video media with loomie characters on learning the history of the Cold War material was declared very feasible and very good for use in the learning process